Oncoplastic volume displacement surgical techniques for early primary breast cancer: A case series - Osama Eldamshety; Ahmed Lamey; Khalid Ahmed Ismail; Taha Ahmed Esmail; Mohamed Tolba; Reda Fawzy Ali (Journal of the Pakistan Medical Association, 2023)
Oncoplastic breast surgery (OPS) is a new strategy for expanding breast-conserving surgical options, lowering mastectomies rates, and preventing deformities. OPS is based on the use of plastic surgical reconstruction after breast cancer removal. The study aims to assess volume displacement oncoplastic procedures for early primary breast cancer in terms of recurrence and cosmoses. A case series study was done on 20 patients with early breast cancer who underwent oncoplastic volume displacement techniques in the period from March 2019 to March 2021 in Kafrelsheikh University Hospital, Egypt. OPS techniques included were Racquet, Benelli, Batwing and Grisotti technique. The study concluded that OPS are oncologically safe (100%) with no recurrence and a better aesthetic outcome (90%). Keywords: Mastectomy, Breast Cancer, Plastic, Oncoplastic.